2015
DOI: 10.7324/japs.2015.50710
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Pharmacognostic and Microscopic Analyses of the Leaves of Clerodendrum polycephalum Baker

Abstract: Phytochemical, pharmarcognostic and microscopy analysis were carried out on the leaves of Clerodendrum polycephalum Baker in order to determine the secondary metabolites present in the plant and the pharmacognostic parameters and microscopic structures of the leaf of the plant. The phytochemical screening indicated the presence of carbohydrate, reducing sugar, tannins, saponins, flavonoids, resins, balsams, alkaloid and phlobatannins and the absence of monosaccharide, combined reducing sugar, pentose sugar, ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Several studies have found that natural antimicrobials derived from plants are effective against multidrug-resistant bacteria. As a result, research needs to be conducted to reveal plant based novel treatment strategies (Egharevba et al, 2015;Abuga et al, 2021). Interestingly, natural compounds account for over 80% of antibacterial, immunosuppressive, cardiovascular drugs and 60% of cancer treatments in the market (WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that natural antimicrobials derived from plants are effective against multidrug-resistant bacteria. As a result, research needs to be conducted to reveal plant based novel treatment strategies (Egharevba et al, 2015;Abuga et al, 2021). Interestingly, natural compounds account for over 80% of antibacterial, immunosuppressive, cardiovascular drugs and 60% of cancer treatments in the market (WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the development of novel antibiotics against UTI causing pathogens, resistance towards the drugs have been observed in the host. Several studies have showcased that natural anti-microbials derived from plants are effective against the UTI causing multidrug-resistant bacteria (Egharevba et al, 2015). Accordingly, appropriate steps are needed to decrease the dilemma of controlling the use of antibiotics, promoting research to explain the genetic mechanisms of resistance adequately and continuing investigations to reveal new medicines (Abuga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves are decussate (whorled), white flowers, sepals usually connate, lobes are unequal [4]. The phytochemical components [5] and antimalarial activities [6] of C. polycephalum have been reported.…”
Section: Introductionmentioning
confidence: 99%